2012
DOI: 10.1044/1059-0889(2012/12-0013)
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Systematic Review of Amplitude Compression in Hearing Aids for School-Age Children With Hearing Loss

Abstract: Purpose Two clinical questions were developed: one addressing the comparison of linear amplification with compression limiting to linear amplification with peak clipping, and the second comparing wide dynamic range compression with linear amplification for outcomes of audibility, speech recognition, speech and language, and self- or parent report in children with hearing loss. Method Twenty-six databases were systematically searched for studies addressing a clinical question and meeting all inclusion criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…We searched 26 databases (e.g., PubMed, CINAHL, PsycINFO, ERIC) from January to April 2010 using keywords related to hearing loss, children, and amplification (e.g., hearing aid, hearing instrument, amplification, child, frequency compression ). A full list of the searched databases and search terms are included in a concurrent review within this series, McCreery, Venediktov, Coleman, and Leech (2012). We examined reference lists of all full-text articles retrieved from the initial search to identify additional relevant articles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We searched 26 databases (e.g., PubMed, CINAHL, PsycINFO, ERIC) from January to April 2010 using keywords related to hearing loss, children, and amplification (e.g., hearing aid, hearing instrument, amplification, child, frequency compression ). A full list of the searched databases and search terms are included in a concurrent review within this series, McCreery, Venediktov, Coleman, and Leech (2012). We examined reference lists of all full-text articles retrieved from the initial search to identify additional relevant articles.…”
Section: Methodsmentioning
confidence: 99%
“…We examined reference lists of all full-text articles retrieved from the initial search to identify additional relevant articles. One author looked for articles citing the studies accepted for inclusion (see McCreery et al, 2012) and searched in the EBSCO database for literature published by 26 prolific authors. The overarching search for the series of reviews was initially completed from January to April 2010; however, given the size and scope of the review series as well as the lapse of time with report of results, the search was updated to include studies published through July 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued developments in signal processing and increasing miniaturization have increased the performance of hearing aids and their acceptance among patients. 85, 86 For example, the maximum gains for digital in-the-ear, in-the-canal and completely-in-canal aids are about 55–65 dB, 45–55 dB and 35–50 dB, respectively. Nearly all hearing aids are digital and programmable and, therefore, can be customized to the characteristics of the patient’s hearing.…”
Section: Managementmentioning
confidence: 99%
“…Research with adults has suggested that both inadequate and excessive amplitude compression can negatively impact speech-recognition abilities for listeners who wear HAs (Brennan and Souza, 2009; Jenstad and Souza, 2007). While studies with children suggest that appropriately prescribed amplitude compression can improve speech recognition compared with linear amplification (Jenstad et al, 1999; or see McCreery et al, 2012 for review), inadequate or excessive amplitude compression might result in differences in audibility for speech that are only apparent when assessing multiple input levels. Differences in audibility across input levels could negatively affect perception in children with hearing loss.…”
Section: Introductionmentioning
confidence: 99%